PENERAPAN PAJAK PENGHASILAN (PPH) PASAL 21 DENGAN TARIF EFEKTIF RATA-RATA (TER) PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN KOTA BANJARMASIN - Syadella Nur Aqilla; Melinda Wijaya; Hamdani (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study aims to determine how the calculation and deduction scheme for Income Tax Article 21 (PPh 21) uses the average effective rate calculated and deducted by the agency, and whether it complies with the new tax regulations. This research is expected to contribute to increasing insight and knowledge, and serve as a reference source for further research on taxation in local government agencies. The findings of this study indicate that the method before TER uses a more complex progressive calculation, the method after using TER for income tax calculations for ASN, and the TER standard bring significant benefits in the form of administrative simplification, time savings, reduced calculation risks, and legal certainty. Therefore, better socialization is needed to expand the application of TER, improve treasurer competency, utilize and implement systems, conduct periodic evaluations, and coordinate with local Tax Offices (KPP). Income Tax (PPh), Average Effective Rate (TER), Civil Servants, Banjarmasin City Education Office.